Automated Tracking Approaches for Studying Online Media Use: A Critical Review and Recommendations. Issue 2 (3rd April 2022) - Christner, Clara; Urman, Aleksandra; Adam, Silke; Maier, Michaela
ABSTRACT: With the increasing importance of online information environments, researchers have started investigating direct measures of online media use, such as online tracking. Most existing studies using tracking data have so far relied on commercial solutions, but these have limitations in terms of their costliness, replicability, and applicability to certain research questions. Hence, different research groups are developing their own tracking solutions for academic purposes. In this paper, we provide a critical review and classification of the existing approaches, apt to guide research decisions on the appropriate tracking approach and tool. First, we develop criteria to distinguish different user-centric desktop and mobile tracking approaches and tools (types of information, technical complexity, privacy implementation, user experience, and availability). Second, we describe different tools and approaches – separately for desktop and mobile tracking – with concrete examples and evaluate them using the aforementioned criteria. Finally, we discuss how different mobile and desktop tracking solutions can complement each other and provide recommendations for future research.